Structural model of repeating purchase in training institute: the effect of satisfaction, price, and service quality - Ronny Kountur; Aprihatiningrum Hidayati; Siti Nuraisyah Suwanda (Cogent Business & Management, 2024)
Repeat purchases are an important element in marketing because they increase revenue. For commercial training institute, revenue is also important. Studies have shown that price of an initial purchase relates to repeat purchases; however, the strength of this relationship may depend on several variables. This study aims to determine whether satisfaction and service quality can moderate the relationship between price and repeat purchases specifically in a training industry. We analyzed 90 courses offered by a training institute. Using the partial least squares statistical technique, we find that the price of training predicts repeat purchases. The relationship between price and repeat purchases strengthens as satisfaction improves but not service quality. However, both satisfaction and service quality had a positive effect on repeat purchases. Therefore, in addition to the fee to attend training, training institutes need to improve participants' satisfaction and service quality, thus improving the firm's repeat purchase.
Keywords: 650; Customer satisfaction; partial least square; price; repeat purchase; service quality